A Freedom Budget for All Americans: Recapturing the Promise of the Civil Rights Movement in the Struggle for Economic Justice Today - Taylor, Kerry (Labour / Le Travail, 2015)
The article reviews the book, "A Freedom Budget for All Americans: Recapturing the Promise of the Civil Rights Movement in the Struggle for Economic Justice Today," by Paul Le Blanc and Michael D. Yates.